Favourable outcomes of repeat one-stage exchange for periprosthetic joint infection of the hip. (1st January 2022) - Liechti, Emanuel F.; Neufeld, Michael E.; Soto, Fernando; Linke, Philip; Busch, Sophia-Marlene; Gehrke, Thorsten; Citak, Mustafa
Abstract : Aims: One-stage exchange for periprosthetic joint infection (PJI) in total hip arthroplasty (THA) is gaining popularity. The outcome for a repeat one-stage revision THA after a failed one-stage exchange for infection remains unknown. The aim of this study was to report the infection-free and all-cause revision-free survival of repeat one-stage exchange, and to investigate the association between the Musculoskeletal Infection Society (MSIS) staging system and further infection-related failure. Methods: We retrospectively reviewed all repeat one-stage revision THAs performed after failed one-stage exchange THA for infection between January 2008 and December 2016. The final cohort included 32 patients. The mean follow-up after repeat one-stage exchange was 5.3 years (1.2 to 13.0). The patients with a further infection-related failure and/or all-cause revision were reported, and Kaplan-Meier survival for these endpoints determined. Patients were categorized according to the MSIS system, and its association with further infection was analyzed. Results: A total of eight repeat septic revisions (25%) developed a further infection-related failure, and the five-year infection-free survival was 81% (95% confidence interval (CI) 57 to 92). Nine (28%) underwent a further all-cause revision and the five-year all-cause revision-free survival was 74% (95% CI 52 to 88). Neither the MSIS classification of the host status (p = 0.423) nor the limb status (p = 0.366) was significantly associated with further infection-related failure. Conclusion: Repeat one-stage exchange for PJI in THA is associated with a favourable five-year infection-free and all-cause revision-free survival. Notably, the rate of infection control is encouraging when compared with the reported rates after repeat two-stage exchange. The results can be used to counsel patients and help clinicians make informed decisions about treatment. With the available number of patients, further infection-related failure was not associated with the MSIS host or limb status. Cite this article: Bone Joint J 2022;104-B(1):27–33.